Legal Implication on Relaas: Conventional Court Summons by Registered Letters - Nur Aini, Alya Septira; Mardiananingrum T.V.M, Sri Maharani; Wahyudi, Eko (Fakultas Hukum Universitas Sultan Ageng Tirtayasa, 2024)
The issuance of PERMA No. 7 of 2022 has led to a shift in the implementation of conventional summons to using registered letters. The details of this change are further explained in SK. KMA 363/KMA/SK/XII/2022, which has implications for society. Society benefits from a more effective and efficient implementation, leading to reduced costs. However, challenges arise regarding the non-receipt of registered letters by parties involved in court proceedings. This study aims to analyze the legal implications of summons implementation based on Civil Procedure Law and PERMA No. 7 of 2022 along with SK KMA 363/KMA/SK/XII/2022. It also seeks to analyze the legal protection available for affected parties. This research adopts a normative juridical approach, utilizing both primary and secondary sources of data. Data collection methods include literature review and interviews, followed by descriptive analysis. The research findings indicate that the implementation of summons through registered letters lacks clear legal information or regulations regarding legal protection, highlighting the need for legal safeguards for aggrieved parties.